Akselerasi Pemasaran Digital UMKM Produk Bayi Melalui Integrasi Branding, Strategi Konten, Live streaming, dan Optimasi Marketplace di Bandung - I Gusti Ngurah Dwi Wiryawan; Debby Kania Bustami; Muhammad Sulaiman; Meylin Siahaan; Mifta Fauziah; Min Hatul Maula; Muhammad Rizky Maulana (LPMP Imperium, 2026)
Changes in consumer behavior in the digital space require micro, small, and medium enterprises (MSMEs) to manage marketing activities in a more structured and integrated manner. This community service program aimed to strengthen the digital marketing of a baby product MSME through the integration of branding, content strategy, live streaming, and marketplace optimization. The method employed was a participatory approach with gradual interventions, including initial diagnosis, strategy design, implementation, monitoring, and evaluation. The results showed improvements in brand identity, clearer functions of each digital channel, increased content consistency, and the effective use of live streaming as a medium for interaction and consumer trust-building. The intervention also positively affected sales performance. Average monthly revenue increased from IDR 289,212 to IDR 1,259,342, while the number of products sold rose from 12 to 79 units per month. It can be concluded that the integration of branding, content, live streaming, and marketplace optimization was able to enhance digital visibility, strengthen consumer trust, and increase sales conversion for the baby product MSME. In addition, the program helped the business partner establish a clearer operational foundation for managing digital promotion activities.